2020
DOI: 10.3389/fpsyg.2020.00118
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Communication System: Gesture and Language Acquisition in Typically Developing Children and Children With LD and DLD

Abstract: Gesture and language development are strongly connected to each other. Two types of gestures in particular are analyzed regarding their role for language acquisition: pointing and iconic gestures. With the present longitudinal study, the predictive values of index-finger pointing at 12 months and the comprehension of iconic gestures at 3;0 years for later language skills in typically developing (TD) children and in children with a language delay (LD) or developmental language disorder (DLD) are examined. Forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 68 publications
1
15
0
8
Order By: Relevance
“…As for the identification of early predictors (Q1), some studies examined the role of biological and environmental risk factors for DLD [ 75 , 76 , 77 , 78 , 79 ] and many provided potentially useful data about early gestural, communicative, lexical, and grammatical predictors [ 75 , 76 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…As for the identification of early predictors (Q1), some studies examined the role of biological and environmental risk factors for DLD [ 75 , 76 , 77 , 78 , 79 ] and many provided potentially useful data about early gestural, communicative, lexical, and grammatical predictors [ 75 , 76 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Current research has demonstrated that co-speech gestures are tightly linked to speech production and perception, suggesting that the two modalities are very closely intertwined in creating meaning and make up a well-integrated communicative system (see [4][5][6], and many others). Previous studies focusing on referential gestures have shown that children's gestures serve as forerunners of future linguistic skills in many populations including not only TD children (e.g., [7][8][9]; see [10] for a review), but also late talking toddlers (e.g., [11]), and children with an Autism Spectrum Disorder (ASD) diagnosis (e.g., [12][13][14]; see [15] for a review). It has also been well established by a variety of studies that referential gestures have a positive effect on adults' and children's cognitive and linguistic abilities (see [16] for a meta-analysis review), boosting memory recall, for example, in TD children [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, children of 20–21 months of age were less able to employ such novel symbolic gestures. Moreover, symbolic gesture comprehension by age three seems to be predictive for later grammar skills (Lüke et al, 2020). Considering all this, it is not surprising that children begin to use symbolic gestures as building blocks of their linguistic constructions when starting to master the early rules of grammar.…”
Section: Resultsmentioning
confidence: 99%